Synthesized activated-biochar and modified-fly ash curbed Cd and Pb uptake in polluted soils and wastewater-irrigated wheat (Triticum aestivum) - SAHA, MADHUMONTI; BISWAS, PABITRA KUMAR; SAHA, JAYANTA KUMAR; SARKAR, ABHIJIT; MANDAL, SANDIP; YADAV, DINESH KUMAR; LENKA, SANGEETA; COUMAR, M VASSANDA; MANDAL, ASIT (The Indian Journal of Agricultural Sciences, 2025)
Wastewater-irrigation for crops becomes inevitable due to freshwater scarcity, which tends to develop lead (Pb) and cadmium (Cd) toxicity in wastewater-irrigated crops and soils. Therefore, for effective removal of Pb and Cd, an ecological strategy is needed. The present study was carried out during winter (rabi) season of 2023–2024 at ICAR-Indian Institute of Soil Science, Bhopal, Madhya Pradesh aimed to prepare steam-activated wheat straw biochar (SABC), and microwave-assisted alkali-infused fly ash (MMFA); to assess their effect on the Pb and Cd uptake by wheat (Triticum aestivum L.) in polluted- and wastewater-irrigated soils. Results revealed that SABC and MMFA amendments significantly improved plant growth compared to control and unamended soils. The MMFA and SABC reduced the Cd and Pb uptake, respectively by the above- and below-ground biomass of wheat. The addition of SABC considerably raised the pH and SOC of the soil by 0.18 units and 26%, respectively over control, polluted- and wastewater-irrigated soils. The SABC and MMFA amended soils, reduced the DTPA-extractable Pb and Cd by 58–72% and 35–61%, respectively. Furthermore, assessment of the translocation factor (TF) and bioconcentration factor (BCF) also support the capacity of SABC and MMFA to immobilize Pb and Cd in soil and lower their phytoavailability in contaminated soil, thereby reducing concerns related to food security.